ETHNO-RELIGIOUS CONFLICT: A THREAT TO BENEVOLENT INTERGROUP RELATIONS IN WUKARI METROPOLIS, TARABA STATE, NIGERIA - Rosemary Onchi Daniel; Ajiyitu Bako (International Studies Journal)
Globally, there are variant patterns of intergroup relations that determines when interaction and contact between individuals and groups in the society produces benevolent or malevolent outcomes.In recent times, the growing interest for political and economic domination among the major ethnic groups has resulted in power tussle.This study examines the ethno-religious conflict and its effects on intergroup relations in Wukari Metropolis, a multi-ethnic society in Nigeria. The aim is to understand the patterns of intergroup relations and the impact of ethno-religious conflicts on social cohesion. The conflict theory is employed as a theoretical framework to explain the phenomenon. A simple random sampling technique was used to select wards, and the Tare Yamane formula determined the sample size. Data was collected through questionnaires from 391 respondents using quantitative methods. The findings reveal that ethno-religious conflicts in Wukari Metropolis are intense and centered around competition for limited resources such as land, political positions, economic resources, natural resources, and human resources. The effects of these conflicts include segregation, underdevelopment, malevolent relations, and loss of lives. The study recommends inclusive distribution of political positions, economic resources, human resources, and natural resources to foster relative peace and accommodate the diverse population in Wukari Metropolis.